Utilizing E-book Storytelling and Meal Preparation Activities to Foster Food Literacy in Early Childhood: A Systematic Literature Review - Andriani, Mia; Mustapa, Noviana; Syarah, Erie Siti (Universitas Negeri Makassar, 2025)
Using a Systematic Literature Review (SLR) approach, this study aims to examine how e-book-based storytelling and meal preparation tasks help to boost food literacy in young children. Food literacy is essential for promoting lifelong well-being and establishing good eating patterns. Still, especially in early childhood education in Indonesia, integrated pedagogical methods combining digital storytelling with actual cooking activities are hardly ever used. This review analyzed fifteen peer-reviewed papers published between 2020 and 2025, gathered from Scopus, ScienceDirect, and Mendeley Research as well as other sources. According to the data, preschoolers are much more inclined to recognize, taste, and embrace nutritious food selections like fruits and vegetables when interactive e-books with vibrant photos and customized stories are employed. Concurrently, experiential learning helps kids develop their practical abilities, attitudes, and food knowledge through hands-on involvement in food preparation chores. Combining these two methods helps us to develop a comprehensive, interesting, and developmentally appropriate plan to promote food literacy in young children. This review offers insightful viewpoints for educators and politicians wanting to develop more participative and contextually suitable strategies in early childhood settings.